2014
DOI: 10.1039/c4cc04876h
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of the high capacitance of nitrogen-containing carbon nanotubes in acidic and alkaline electrolytes

Abstract: The preparation of nitrogenated carbon nanotubes (N-CNT) using pyridine as a carbon precursor resulted in an eight-times increase in gravimetric capacitance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 26 publications
1
63
0
Order By: Relevance
“…As can be seen, KUA-CONH2 Table 1) this difference cannot be explained by diffusional problems along the porosity. Then, the improvement found for KUA-N should be related to the generation of electron-donor nitrogen functionalities [8] or to the decrease of detrimental electron-withdrawing oxygen groups improving the conductivity of the material. This positive effect of the conversion of oxygen groups into nitrogen functionalities is not observed in KUA-CONH 2 due to the previous generation of a large amount of carboxylic acids during the oxidation treatment with nitric acid.…”
Section: Figure 5amentioning
confidence: 99%
See 2 more Smart Citations
“…As can be seen, KUA-CONH2 Table 1) this difference cannot be explained by diffusional problems along the porosity. Then, the improvement found for KUA-N should be related to the generation of electron-donor nitrogen functionalities [8] or to the decrease of detrimental electron-withdrawing oxygen groups improving the conductivity of the material. This positive effect of the conversion of oxygen groups into nitrogen functionalities is not observed in KUA-CONH 2 due to the previous generation of a large amount of carboxylic acids during the oxidation treatment with nitric acid.…”
Section: Figure 5amentioning
confidence: 99%
“…Likewise, the presence of nitrogen on the surface of activated carbons improves the performance of activated carbon as electrodes of supercapacitors by increasing the wettability of the surface, the electrochemical stability, the conductivity or the contribution of pseudocapacitive processes [5][6][7][8]. Inversely to the ubiquity of surface oxygen groups, nitrogen functionalities are not as easily introduced in the structure of carbon materials, and the development of new procedures for obtaining nitrogencontaining porous carbons has therefore attracted a great interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was pointed out that pyridinic nitrogen and pyrrolic nitrogen were the most effective in a double layer formation while quaternary-N and pyridinic-N-oxides improved the capacitance due to their positive charge [43]. Moreover, the nitrogen groups showed an enhancement in the capacitance in neutral and basic electrolytes [15,26,44].…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Moreover, it was demonstrated that this high nitrogen amount prevails even after the chemical activation. It is known that nitrogen groups change the electrochemical properties, such as electron-donor character, conductivity and capacitance behavior [9,[24][25][26]. The improvement of these electrochemical properties together with the control of the porous texture, would give suitable carbon materials to enhance the capacitors performance.…”
Section: Introductionmentioning
confidence: 99%